Bank Size, Investment Financing, Islamicity Performance Index dan Penerimaan Zakat Perbankan Syariah - Putra, Rosyid Nur Anggara (UIN Sunan Kalijaga Yogyakarta, 2022)
Research Aims: Islamic banking has a function as a social agent. In carrying out their function as social agents, Islamic banks have the task of collecting and managing zakat funds. This study aims to determine the internal factors of Islamic banks that affect the acceptance of zakat in Islamic banks. Internal factors of Islamic banks are measured by bank size, mudharabah financing, musyarakah financing, buying and selling financing, and the Islamic performance index which is measured by profit sharing ratio, equitable distribution ratio, and Islamic vs non-Islamic income ratio. Methodology: The population of this study is Islamic banks in Indonesia for the period 2013-2021 with a total sample of 8 banks. The sampling technique is the purposive sampling method by taking data from the financial statements of Islamic banks. The analysis technique uses multiple linear regression. Research Findings: The results showed that bank size and buying and selling financing had a positive effect on zakat receipts. Meanwhile, mudharabah financing, musyarakah financing, profit sharing ratio, equitable distribution ratio, and Islamic vs non-Islamic ratio do not affect zakat receipts. Keywords: Islamic Banking, bank size, Investing Financing, Islamicity Performance Index, Zakat